FINITE ELEMENT ANALYSIS OF SLOPE STABILITY REINFORCED WITH CORRUGATED CONCRETE SHEET PILE - Dewa Ngakan Putu Ananda Parwita; I Gede Ngurah Arya Yudistira (Universitas Udayana, 2025)
Slope instability is a major geotechnical challenge in coastal and soft ground areas, often leading to structural damage and safety hazards. This study presents a numerical analysis of slope stability in Tanjung Batu, East Kalimantan, focusing on the effect of using Corrugated Concrete Sheet Pile (CCSP) as a slope reinforcement system. The analysis was conducted using PLAXIS 2D, applying the finite element method and strength reduction technique to evaluate changes in safety factor due to the installation of CCSP. The results show that the implementation of CCSP reinforcement significantly improves the slope's factor of safety, indicating increased stability under site-specific loading and soil conditions. In addition, deflection and structural performance evaluations of the selected sheet pile type (CCSP W-400) reveal that the maximum bending moment remains below both the cracking and ultimate moment capacities, confirming the adequacy of the structural design. This research demonstrates that CCSP is not only effective in improving slope stability but also structurally reliable under expected field conditions. The findings support the use of prefabricated concrete sheet piles as a practical and efficient solution for slope stabilization in similar geotechnical environments. Further studies incorporating field data and long-term performance monitoring are recommended.